AKUNTABILITAS DAN TRANSPARANSI LAPORAN KEUANGAN BAZNAS TERHADAP TINGKAT KEPERCAYAAN MUZAKKI DI KABUPATEN PEKALONGAN - Rizky Uzwatun Khasanah; Astri Afifatul Khikmah; Gunawan Aji (CV. Denasya Smart Publisher, 2026)
This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation, involving BAZNAS administrators and active muzakki in Pekalongan Regency. Data analysis was conducted using an interactive analysis model comprising data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The findings indicate that BAZNAS Pekalongan Regency has implemented accountability through the preparation of financial statements in accordance with PSAK 109 standards, the conduct of audits, and the submission of accountability reports to relevant stakeholders. Transparency is manifested through the publication of financial reports and zakat fund distribution activities across various media platforms. The implementation of accountability and transparency has a positive influence on muzakki’s perceptions and levels of trust. However, this study also reveals that muzakki’s understanding of the content of financial statements remains limited. Therefore, efforts are required to enhance the quality of information presentation and communication to ensure that financial information is more easily understood by the public.